2023
DOI: 10.3390/microorganisms11081956
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Gestational Diabetes Mellitus and Infections in Pregnancy—Systematic Review and Meta-Analysis

Enav Yefet,
Aviv Bejerano,
Rula Iskander
et al.

Abstract: We conducted a systematic review and meta-analysis to evaluate the association between gestational diabetes mellitus and infections during pregnancy. We included cross-sectional, case-control, cohort studies and clinical trials, evaluating the frequency of infections in women with and without gestational diabetes mellitus. A search was conducted in Embase, PubMed, and Web of Science electronic databases and by manually searching references, until 23 March 2022, resulting in 16 studies being selected for review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…A study in South India showed that pregnant women with GDM were three (3) times more likely to develop UTI than their counterparts who did not have GDM (P = 0.051, OR = 3.2), 31 which was consistent with a systemic review that showed similar results where there was a significant association between GDM and UTI but not vaginal candidiasis. 32 The explanation for this could be that gestational diabetes compromises the immune system, predisposing it to infections such as UTI. 33,34 One of our limitations was the lack of funding, as we were unable to follow our participants to study maternal and newborn outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A study in South India showed that pregnant women with GDM were three (3) times more likely to develop UTI than their counterparts who did not have GDM (P = 0.051, OR = 3.2), 31 which was consistent with a systemic review that showed similar results where there was a significant association between GDM and UTI but not vaginal candidiasis. 32 The explanation for this could be that gestational diabetes compromises the immune system, predisposing it to infections such as UTI. 33,34 One of our limitations was the lack of funding, as we were unable to follow our participants to study maternal and newborn outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Offspring exposed to GDM have an increased risk of macrosomia, fetal growth restriction, preterm birth, and neonatal metabolic dysfunction. In the long-term both mothers and babies have an increased risk of developing metabolic diseases such as type 2 diabetes mellitus (T2DM) and cardiovascular disease [ 5 , 6 , 7 , 8 ]. Despite a well-established association between GDM and unfavorable maternal and neonatal outcomes [ 5 , 6 , 7 ], the mechanisms that underlie this link remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%